Analisa Pemanfaatan dan Peran Software Open-source bagi Mahasiswa Universitas Abdurrab - Salamun, Salamun; Sukri, Sukri (Jurnal Buana Informatika, 2021)
Abstract. Analysis of Software Utilization and the Role of Open-source for Abdurrab University Students. Open-source software can be acquired by downloading it for free from the internet, where the software code is published to the public or internet users. Generally, people will fix the software weaknesses and modify its display or language. Then, the repaired software is uploaded and published back to the internet. At the same time, other people will also download this open-source software application and fix other flaws. The purpose of this study was to determine the benefits and roles of open-source software for Abdurrab University students. The results of this study indicate an increase in student interest in using open-source applications and the influence, utilization, and role of open-source software for Abdurrab University students. The conclusion in this study is that open-source software still plays an important role for students because it is very helpful in various aspects to support learning.Keywords: Internet, Software, University of Abdurrab, open-sourceÂ Abstrak. Open-source software dapat dimiliki dengan cara mengunduh secara gratis dari internet, yang mana kode software dipublikasikan ke publik atau pengguna internet. Umumnya, orang akan memperbaiki kelemahan-kelemahan software tersebut dan memodifikasi tampilan atau bahasanya. Lalu, software yang diperbaiki tersebut diunggah dan dipublikasikan kembali ke internet. Pada saat yang sama, orang lain juga akan mengunduh aplikasi software open-source ini dan memperbaiki kelemahan-kelemahan lain. Tujuan dari penelitian ini adalah mengetahui manfaat dan peran open-source software bagi mahasiswa Universitas Abdurrab. Hasil penelitian ini memperlihatkan adanya peningkatan minat mahasiswa dalam menggunakan aplikasi open-source dan pengaruh, pemanfaatan, serta peran software open-source bagi mahasiswa Universitas Abdurrab. Kesimpulan pada penelitian ini ialah open-source software masih berperan penting bagi mahasiswa karena sangat membantu dalam berbagai aspek untuk mendukung pembelajaran.Kata Kunci: Internet, Software, Universitas Abdurrab, open-source